2006
DOI: 10.1038/sj.jcbfm.9600288
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Cerebral Tissue Response to Subventricular Zone Cell Transplantation Measured by Iterative Self-Organizing Data Analysis Technique Algorithm

Abstract: To investigate the changes of the ischemic lesion in rat brain after subventricular zone (SVZ) cell transplantation and the influence of the grafted cells on the appearance of angiogenesis, SVZ cells, superparamagnetically labeled, were intracisternally transplanted into the rat brain 48 h after onset of embolic stroke. A complete set of magnetic resonance (MR) images was acquired for all animals with (n = 8) and without (n = 3) cell grafting at approximately 24 h, 72 h, and weekly for 6 weeks after stroke. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…6 In the stroke rats treated with neural progenitor cells, the transplanted cells arrive at their destination within 1 week after grafting and angiogenesis activity occurs in sites either adjacent to or surrounded by the grafted cells. 22 In this situation, it is difficult to use the T 2 * to detect angiogenesis because the grafted cells are labeled with iron. While the other pattern, for control animals treated with saline, demonstrated that the regional K i values remained elevated from 1 to 6 weeks after stroke, as shown in the first row of K i maps in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…6 In the stroke rats treated with neural progenitor cells, the transplanted cells arrive at their destination within 1 week after grafting and angiogenesis activity occurs in sites either adjacent to or surrounded by the grafted cells. 22 In this situation, it is difficult to use the T 2 * to detect angiogenesis because the grafted cells are labeled with iron. While the other pattern, for control animals treated with saline, demonstrated that the regional K i values remained elevated from 1 to 6 weeks after stroke, as shown in the first row of K i maps in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…3,[5][6][7]62,65 These treatments revise brain architecture, including vascular changes associated with angiogenesis, neurogenesis, glial changes, reduction of scar tissue with treatment, increased presence of progenitor and mature oligodendrocytes after treatment, and changes in the white matter. 14,11,27,[65][66][67] Aspects of brain structural and angiogenic remodeling may be visible on MRI. 12,67,68 …”
Section: Mri Monitoring Of Plasticity and Recovery After Strokementioning
confidence: 99%
“…14,11,27,[65][66][67] Aspects of brain structural and angiogenic remodeling may be visible on MRI. 12,67,68 …”
Section: Mri Monitoring Of Plasticity and Recovery After Strokementioning
confidence: 99%
“…Chen et al also found that the K trans map can predict clinical outcomes after stroke. K trans , as well as measurements from other sequences in MR, also confirmed the location and the size of the area of revascularization and angiogenesis [31]. Similar to its usefulness in detecting tumor angiogenesis, K trans is a sensitive parameter for the detection of early brain angiogenesis in post-stroke patients.…”
Section: Application In Ischemic Brain Injurymentioning
confidence: 66%